Integrasi Tafsir dan Sains: Kajian Literatur - Labib, Muchsin; Nikmah, Zahra Awwalun (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2025)
Science and the Quran share a close, complementary relationship, historically and in contemporary thought. Classically, the Quran contained diverse knowledge relevant through time, including language, law, creed, worship, ethics, and knowledge of the universe. The Quran encourages human reason and critical thinking via observation and experimentation, as practiced by early Muslim scientists.In modern views, integrating science and the Quran extends beyond the physical to the spiritual, strengthening Muslim faith and morals. The Quran stresses ethics in science, teaching trustworthiness in research, integrity, and social responsibility. For instance, the benefits of pomegranates in the Quran are scientifically proven as good antioxidants, showing harmony between revelation and science.Through tawhid and scientific ethics, science and religion can mutually support human benefit and the relationship with God. This qualitative literature study indicates significant integration of Quranic values and modern science principles. Quranic interpretation and science have the potential to mutually enrich a holistic understanding of knowledge. Based on these findings, further in-depth studies regarding the integration of Quranic and scientific perspectives are highly recommended to enhance the understanding and implementation of this integrative approach in various scientific contexts.